Pengaruh Dimensi Fraud Hexagon terhadap Financial Statement Fraud - Siregar, Anitaria; Murwaningsari, Etty (Jurnal Kajian Akuntansi, 2022)
AbstractThe purpose of this research is to analyze the influence of fraud factors of fraud hexagon (S.C.C.O.R.E) towards fraudulent financial statement. Fraudulent financial statement is measured by using Beneish M-Score Model. There are six variables of fraud hexagon in this study that are considered to have  influenced fraudulent financial statement. The variables consist of stimulus (financial stability), capability (competency), collusion (project with government), opportunity (effective monitoring), rationalization (historical restate frequency), and ego (company existence). The population are  manufacture companies listed on the Indonesia Stock Exchange from 2016 to 2020. The research samples are taken by purposive sampling with total observation 280. The results of the research show that stimulus (financial stability), capability (competency) and collusion (project with government) have a significant effect towards the fraudulent financial reporting, while opportunity (effective monitoring), rationalization (historical restate frequency) and ego (company existence) do not have a significant effect towards the fraudulent financial reporting. The implication of this research result is that the dimension of collusion (project with government) has a significant effect but with the negative coefisien, which means that the hyphotesis rejected. This result gives the implication that further analysis needs to be done for proxy used  for this dimension, as having project with government the likelihood for fraud is reduced. This research uses ineffective monitoring of audit committee as control variable.Keywords: collusion; fraudulent financial statement;  fraud hexagon; fraud triangle; S.C.C.O.R.E.Abstrak Penelitian bertujuan untuk menganalisis pengaruh dari faktor-faktor fraud hexagon (S.C.C.O.R.E) terhadap fraudulent financial statement. Fraudulent financial statement  diukur dengan menggunakan Beneish M-Score Model. Enam variabel fraud hexagon dalam penelitian ini dipertimbangkan mempengaruhi fraudulent financial statement. Variabel-variabel tersebut terdiri dari stimulus (financial stability), capability (competency), collusion (project with government), opportunity (effective monitoring), rationalization (historical restate frequency), dan ego (company existence). Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia untuk periode tahun 2016-2020. Sampel dalam penelitian ini diambil dengan menggunakan purposive sampling dengan total observasi 280. Hasil dari penelitian ini menunjukkan stimulus (financial stability), capability (competency) dan collusion (project with government) berpengaruh signifikan terhadap fraudulent financial reporting, sementara opportunity (effective monitoring), rationalization (historical restate frequency) dan ego (company existence) tidak berpengaruh signifikan terhadap fraudulent financial reporting. Implikasi dari penelitian ini adalah dari hasil dimensi kolusi (project with government) menunjukkan hasil yang berpengaruh signifikan dengan koefisien yang negatif, sehingga hipotesis untuk elemen ini, ditolak. Hasil ini memberikan implikasi untuk pengembangan proksi pengukuran baru dalam dimensi ini, karenakondisi perusahaan memiliki proyek dengan pemerintah ternyata kecenderungan untuk melakukan fraud-nya berkurang. Penelitian ini menggunakan variabel kontrol ineffective monitoring of audit committee.Kata kunci: collusion; fraudulent financial statement; fraud hexagon; fraud triangle; S.C.C.O.R.E.